INHERENT SIGNAL PREPROCESSING IN THE LINE CCD SENSOR - Kejzlar, Ludek; Fischer, Jan (International Journal of Computing, 2014)
This paper is devoted to the description and practical verification of a new line CCD sensor control method. This method is used for inherent signal preprocessing or processing in line CCD sensor. This new method is suitable for movement compensation, one-frame filtration or two-frame filtration. Because of the similarity between a Non- Recursive Digital Filter with Finite Impulse Response (NRDF FIR) and the new mode we named it FIR mode. Conclusions and hints applicable for operation of line CCD sensor in FIR mode are also included in this paper.